Minicomputers - Sanderson, Peter (Newnes, 2014)
Minicomputers illustrate some of the potential pitfalls and benefits that can be gained if a minicomputer system is chosen wisely. This book is divided into five chapters-introduction, software, programming, selecting the minicomputer system, and applications. This text specifically discusses the advantages of the minicomputer, peripheral devices for minicomputer systems, arithmetical software, and operating systems. The nature of programming language, typical minicomputer assembly language functions, and feasibility study are also elaborated. This monograph likewise covers the preparation of tender, original equipment manufacturers (OEM) applications, and unusual applications of minicomputers. This publication is beneficial to all potential users such as scientists, research workers, process control engineers, and business managers, including educationalists concerned with computer education.